Notes on the Indo-West Pacific shrimp genus Athanopsis Coutière, 1897 (Crustacea, Decapoda, Alpheidae), with the description of a new species associated with echiurans (Annelida, Thalassematidae) - Anker, Arthur (Zootaxa, 2012)
The Indo-West Pacific alpheid shrimp genus Athanopsis Coutière, 1897 is briefly reviewed. Athanopsis platyrhynchusCoutière, 1897, the type species, is reassessed using Coutière’s illustrations and morphological notes scattered throughouthis monograph of the family Alpheidae (Coutière 1899). Athanopsis brevirostris Banner & Banner, 1981, originally de-scribed on the basis of a single immature specimen missing both chelipeds, is reported and illustrated based on fresh ma-terial from Madagascar and southern Japan. Athanopsis gotoi sp. nov. is described based on two fresh specimens fromsouthern Japan, both found associated with thalassematid echiurans, and an additional, older museum specimen from In-donesia. The colour patterns of A. brevirostris, A. gotoi sp. nov., A. saurus Anker, 2011, A. rubricinctuta Berggren, 1991,and A. australis Banner & Banner, 1982, are contrasted to facilitate their identification in the field. A morphology and colour based key to all presently known species of Athanopsis is also provided.